Kedudukan dan Peran Qonun Jinayat sebagai Instrumen Pencegahan Kriminalitas di Provinsi Aceh - Saputra, M Diaz; Maulana, Muhammad Habib; Najmudin, Deden (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Qanun Jinayat is an autonomous regional regulation that only applies in the province of Aceh as a manifestation of the special implementation of Islamic law in Indonesia’s national legal system. This study aims to analyze the position and role of Qanun Jinayat as an instrument for crime prevention in the Aceh region. This study focuses on the normative and functional aspects of Qanun Jinayat in enforcing criminal law based on the principles of Islamic law, as well as assessing its contribution to social stability and public order. The research method used is a qualitative approach with a normative juridical method through a literature study, which includes an analysis of Islamic legal literature, Aceh Qanun Number 6 of 2014 concerning Jinayat Law, and relevant laws and regulations. The results of the study show that the Qanun Jinayat has a strong position as part of the regional legal system recognized within the framework of Aceh’s special autonomy. Its implementation plays a significant role in reducing crime rates through the imposition of sanctions that have a deterrent effect and increase public legal awareness. The innovation offered by this study lies in its strengthened analysis of the position and role of the Jinayat qanun in reducing crime in Aceh. This study contributes to the development of Islamic legal studies in Indonesia, particularly in understanding how Sharia norms can be effectively integrated into the positive legal system through the instrument of the Jinayat Qanun.